Drag Force for Asymmetrically Grafted Colloids in Polymer Solutions - Werner, Matthias; Margaretti, Paolo; Maciołek, Anna (Frontiers in Physics, 2019)
We consider the situation in which a colloidal particle modifies locally the solvent leading to a spatially dependent viscosity. This situation is typical for colloidal particles in crowded environment, for example DNA-grafted particles in a polymer solution, or a hot particle which implies a temperature gradient to a viscous liquid. By means of suitable approximations we calculate the dependence of the friction force on the profile of the local viscosity. Our results show that in the case of axially symmetric viscosity profile the friction force is sensitive to the anisotropy of the viscous profile whereas it is not sensitive to for-ahead asymmetries. Our results are crucial for active microrheology measurements where tracer particles are pulled through complex fluids.